The infaunal clam Polititapes rhomboides exposed to sediment mobilization and seawater warming: Recovery patterns and energetic constraints - Jose M.F. Babarro; Miguel Gilcoto; Nicolás Villacieros-Robineau; Sonia Dios; Maria M. Costa; Camino Gestal; Luc A. Comeau; Hugo Feio (Ecological Indicators, 2024)
Infaunal organisms living within marine sediments can provide valuable information about the effect of key environmental factors, acting as ecological indicators e.g. species composition and diversity, tolerance to pollution, or resilience degree facing abiotic stressors such as wave storm events. These organisms may modify their environment through burrowing behavior, enhancing mixing, and nutrient and oxygen cycling, which are crucial for ecosystem health. Simultaneously, such high-energy events (wave storms) may impair the ecophysiology of organisms, altering trophic interactions in this particular food web. A set of behavioral, ecophysiological, and stress/immune responses were monitored for the infaunal clam Polititapes rhomboides exposed to key abiotic stressors identified in our coasts (Rías Baixas, NW Iberian Peninsula) as drivers of massive mortality events in the past: sediment mobilization disturbance (SM) in the bottom seafloor, and seawater warming (SW). Valve opening was clearly reduced during physical disturbance while minor effects were observed for temperature increase (+3 °C, from 15 °C to 18 °C). Nevertheless, a highly resilient behavior was noted for the shell opening of clams (crucial for vital physiological functions) after each physical disturbance cycle, with similar profiles to organisms kept under control calm scenarios. The physiology of clams was also altered by sediment mobilization, resulting in a decline of clearance rates (feeding activity) but only with regard to short-term periods after disturbance (e.g. hours). In contrast, temperature increase caused clearance rates to also increase significantly, linked to the optimal diet supplemented during the experiment. The combination of both stressors (sediment mobilization and temperature increase simultaneously) resulted in elevated oxygen consumption rates and nitric oxide production by the clams as activated responses to stress. Again, the ability of the clams to recover from physical disturbance and re-burrow after each disturbance cycle was notorious, most likely escaping from warmer seawater. Clams were able to increase feeding activities (clearance rates) when sediment mobilization ceased based on optimal food availability that counterbalanced the increase in metabolic expenditure during disturbance, although far from the energetic uptake capacity of undisturbed clams. Neither mortality nor dramatic metabolic changes were reported for P. rhomboides subjected to physical disturbance and warming proposed in this survey. Optimal food resource availability has been crucial for the clams to recover from abiotic stressors despite the reported energetic vulnerability index (SFG). The stressors investigated here would act at a greater magnitude in the natural environment, with much more heterogeneity regarding to trophic conditions. Changes in the dynamics of coastal areas driven by heterogeneous (high-energy) environments linked to hydrodynamics would affect not only biodiversity maintenance but also the socioeconomic sectors involved and therefore, its comprehension would be crucial for the resilience of natural systems under Agenda 2030 and the Sustainable Development Goals (SDGs).